Overview of different strengthening techniques applied on walls used in historical structures - Miccoli, L. (2012)
Different types of vertical elements, such as masonry, massive walls and timber frame elements, exhibit a different response exposed to the same loading scenario, in particular when it concerns dynamic loading. It is therefore paramount to investigate the principal response of different types of construction with different materials under a variety of loading scenarios. From there, the design of strengthening techniques against earthquakes can be performed. This paper presents the results from experiments, where various retrofitting techniques were tested. The goals were to define and improve laboratory procedures for evaluating the intervention technologies and specifications for laboratory specimens. From this base tests to characterise the experimental behaviour of original and strengthened masonry walls were performed, in order to obtain information on the system performance and the main constitutive laws relevant for modelling. The test campaigns were focused on static tests as well as cyclic tests of unreinforced and reinforced vertical building elements. The study is part of our work in the framework of the ongoing project NIKER funded by the European Commission dealing with improving immovable Cultural Heritage assets against the risk of earthquakes.